Pengaruh Return on Assets (ROA) dan Debt to Equity Ratio (DER) Terhadap Harga Saham Pada PT. Mayora Indah TBK Periode 2011-2020 - Syifa Fauziah; Aria Aji Priyanto (Formosa Journal of Sustainable Research, 2022)
This research was conducted at PT. Mayora Indah, Tbk for the period 2011-2020 aims to examine the effect of return on assets and debt to equity ratio on stock prices. The independent variables are return on assets and debt to equity ratio. The dependent variable is the stock price. This type of research is quantitative with the help of SPSS version 26, the type of secondary data. The test uses classical assumption test, simple linear regression analysis, multiple linear regression analysis, hypothesis testing, and determination test. The results show that partially the return on assets has no effect on stock prices and the debt-to-equity ratio partially affects stock prices. And based on the F test return on assets and debt to equity ratio simultaneously affect stock prices